Modulation of immune functions by oestrogens. Part II - Wilczyński, Jacek R. (Menopause Review/Przegląd Menopauzalny, 2010)
One of the most important functions of oestrogens is modulation of the immune system. By interactions with specific oestrogen receptors ERa and ERb these sex steroid hormones are capable of regulating many aspects of both natural and adaptive immunity. Aging and the hypoestrogenic state can therefore influence immunological functions. Use of drugs belonging to SERM or isoflavons could also modify immune response in post-menopausal women. All those phenomena might influence the risk of cancer initiation and the natural course of tumour growth.